Scorpionato Halide Complexes [(TpPh, Me)Ni–X] [X = Cl, Br, I; TpPh, Me = Hydrotris(3‐phenyl‐5‐methyl‐1‐pyrazolyl)borate]: Structures, Spectroscopy, and Pyrazole Adducts. Issue 3 (23rd December 2014) - Deb, Tapash; Anderson, Caitlin M.; Ma, Huaibo; Petersen, Jeffrey L.; Young, Victor G.; Jensen, Michael P.
Abstract: Pseudotetrahedral scorpionato halide complexes [(Tp Ph, Me )Ni–X] [Tp Ph, Me = hydrotris(3‐phenyl‐5‐methyl‐1‐pyrazolyl)borate] were synthesized by metathesis of Tl(Tp Ph, Me ) and NiX2 (X = Cl, Br, I). Pyrazole adducts [(Tp Ph, Me )Ni(Hpz Ph, Me )(X)] (X = Cl, I) were also obtained. [(Tp Ph, Me )Ni–X] (X = Br, I) are isomorphous with previously reported [(Tp Ph, Me )Ni–Cl], and a new solvated pseudo‐polymorph [(Tp Ph, Me )Ni–Cl]· 2CH2 Cl2 was found in this work. Ni–X bond lengths correspond to ionic radii of the halide ions, but some variations in Ni–Cl and Ni–N bond lengths are respectively attributed to bending of the chloride from the ideal threefold HB··· Ni axis and to the size of the 3‐pyrazole substituents. Electronic spectra were rationalized by means of time‐dependent (TD) DFT calculations on simplified C 3 v ‐symmetric [(Tp)Ni–X] models. Exogenous pyrazole binds to give the pentacoordinate adducts [(Tp Ph, Me )Ni(Hpz Ph, Me )(X)] (X = Cl, I). We obtained a crystal structure of the iodide adduct, as well as that of [(Tp Ph, Me )Ni(Hpz Ph, Me )(Cl)]· 0.5MeCN, isomorphous with a previously reported aquo monosolvate. A hallmark of adduct formation is an intramolecular N–H··· X hydrogen bond between the added pyrazole and the adjacent halide ligand, thus giving rise to a strong IR absorption band. The stretching frequency correlates to the N(H)··· X separation for the range of known adducts. Abstract : Pseudotetrahedral scorpionato halide complexes [(Tp Ph, Me )Ni–X] [X = Cl, Br, I; Tp Ph, Me = hydrotris(3‐phenyl‐5‐methyl‐1‐pyrazolyl)borate] and pentacoordinate pyrazole adducts [(Tp Ph, Me )Ni(HPz Ph, Me )(X)] (X = Cl, I) were synthesized, characterized by X‐ray crystallography and spectroscopy, and simulated by density functional calculations. Analyses of the structures, spectroscopy, and bonding are discussed with respect to the different halides.